Konstruksi Sistem Ekonomi Islam Menuju Kesejahteraan yang Merata - Fahrur Ulum (TSAQAFAH, 2015)
In any economic system, growth and prosperity are the main economic issues. But how to create wealth while creating social justice, then it must be answered by all the systems of the economy. This qualitative study examines the Islamic economic system that is able to create prosperity and social justice to build a noble civilization. The concept of the creation of welfare in Islam is through increased production by giving the prize to anyone who will strive and work. Work is a part of worship. Welfare should be felt by all levels of society through the mechanism of distribution of wealth. This distribution mechanism concerning the mechanism of economic and non-economic mechanism. The economic mechanism is a productive economic activity, followed by production factors provided to society. As for the non-economic mechanism is non-productive activities, for example by way of giving zakat, alms, grants, and others. Both of these mechanisms are outlined in the concept of ownership, ownership management and distribution of wealth in society. Both of these mechanisms must be supported by the role of the state optimally and ethical principals of economics that is sublime. So the welfare and social justice can be realized by working and optimization of the role of the state, ethics sublime and the implementation of economy mechanism and non-economy that spelled out the concept of ownership, ownership management, and distribution of wealth. The Islamic economic system becomes an integral part in building a noble civilization of mankind and has been proven empirically and historically. Empirically, Islamic economy is capable of creating prosperity and staying away from the exploitation of human beings against other human beings. And historically, Islamic economics has been applied for more than a thousand years.